Analisis Pengukuran Faktor Paling Dominan Yang Mempengaruhi Harga Saham Perbankan BUMN Indonesia Periode 2009 – 2018 - Enok Nurhayati; Widya Nur Bhakti Pertiwi (FEB Universitas Sultan Ageng Tirtayasa, 2021)
The puprose of this study is to find out the most dominsnt factors tahst affect the Share Price of Perbankan BUMN in Indonesia. The specific target of this research is able to identify the factors that influence the Share Price. The methode used a quantitative method by analyzing secondary data from financial statement banks published on the stock exchange. There are four banks, namely is Bank Negara Indonesia (BNI), Bank Rakyat Indonesia (BRI), Bank Tabungan Negara (BTN), and Bank Mandiri (BMRI), in wich the four banks are the both population and sample with the study period from 2009 to 2018. Based on the results of the analysys of individual parameter tests (t test) obtained 1) partially CAR significantly influence on HS, 2) partially NPL not significant negative effect on HS, 3) partially LDR not significant negative effect on HS, 4) partially NIM does not have a significant effect on HS, 5) partially ROA has a significant effect on HS, and the stepwise regression test results show that only 2 variables, namely CAR dan ROA are the most dominant influencing the Share Price (HS).